ANALISIS GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA BANK BNI KANTOR CABANG JAKARTA KOTA - Febrianti, Ayuningtyas; Kemas Vivi Andayani (Journal of Research and Publication Innovation, 2024)
decreasing employee performance, therefore it is clear that every company needs an effective leadership style because in this case it also depends on the reliability and ability of employees in operating work units. existing in an organization, effective leadership and the influence and role of leadership are very necessary because in reality the success of an organization is determined by the leadership and leadership style developed in the organization to achieve the goals of the organization. This research was conducted with a problem formulation of how much influence leadership style and work environment have on work productivity at the BNI Jakarta Kota Branch Office. This type of research is a qualitative type of research using interview methods and productivity data collection. From the results of the research data analysis, it was concluded that the influence of the leadership style and work environment applied by the BNI Jakarta Kota Branch Office had a positive effect on increasing employee productivity.